Konstruktionen Europas in der Frühen Neuzeit : Beiträge zur 11. Arbeitstagung der Arbeitsgemeinschaft Frühe Neuzeit - Richter, Susan; Roth, Michael; Meurer, Sebastian (2017)
Global history has long become an established field of research. At the 11th conference of the working group on the Early Modern Period (Historians’ Association, Germany), participants aimed at applying global-history approaches on early modern Europe. “Europe” has consistently been both a subject to and a concept of negotiation processes, which hardly kept to territorial borders or clear-cut topographically or language-bounded areas. The conference proceedings open up new views on geographical and historical imaginations of Europe from within and without, on claims of identity and alterity as well as on the mutability of periphery-centre relations. Moreover, they display the wide range of – internationally well-connected – historical research on the early modern period in Germany.